2014
DOI: 10.1183/09031936.00081314
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular reserve in a piglet model of chronic pulmonary hypertension

Abstract: Right ventricular (RV) response to exercise or pharmacological stress is not well documented in pulmonary hypertension (PH). We investigated the relationship between RV reserve and ventricular-arterial coupling.Surgical ligation of the left pulmonary artery was performed in 13 Large White piglets (PH group), thereafter weekly embolisations of the right lower lobe were performed for 5 weeks. A control group of six piglets underwent sham procedures. Right heart catheterisation and echocardiography were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 33 publications
3
33
1
Order By: Relevance
“…Likewise, the assessment of other echocardiographic parameters (RVFAC) might have provided superior discernment of impaired right ventricular contractile reserve. As noted earlier, GUIHAIRE et al [11] found RVFAC to have a stronger correlation than TAPSE with haemodynamic assessment of contractile reserve. Future studies should also consider assessment of right ventricular strain as a marker of right ventricular contractile reserve.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…Likewise, the assessment of other echocardiographic parameters (RVFAC) might have provided superior discernment of impaired right ventricular contractile reserve. As noted earlier, GUIHAIRE et al [11] found RVFAC to have a stronger correlation than TAPSE with haemodynamic assessment of contractile reserve. Future studies should also consider assessment of right ventricular strain as a marker of right ventricular contractile reserve.…”
mentioning
confidence: 59%
“…In short, GUIHAIRE et al [11] show that the absence of right ventricular contractile reserve is correlated with RV-PA uncoupling at rest in an animal model of PAH, a novel and important finding. However, this study leaves several important questions unanswered.…”
mentioning
confidence: 88%
See 3 more Smart Citations